Nature of critical current and coherent phenomena in granular MoNx thin films - Prokhorov, V. G.; Kaminsky, G. G.; Lee, Y. P.; Kravchenko, I. I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2000)
Investigations of the critical current versus temperature and applied magnetic field were carried out for granular MoNx films. All sampels display a two-stage superconducting transition and can be treated as a percolating network of SNS contacts with a Josephson coupling between grains. The temperature behavior of the critical current for the films studied is the same as the Ic(T) dependence for a SNS junction in the diffusive limit. The value of critical current in a magnetic field is governed by the pinning of Josephson vortices.